Respuesta :
Answer:
y=3x+15
Step-by-step explanation:
y2-y1 6 - 3 3
_____= _______= ______= 3
x2- x1 -3 + 4 1
y - y1 = m(x - x1)
= y -6 = 3( x + 3)
= y -6 = 3x + 9
= y = 3x + 15
Answer:
y = 9x -3
Step-by-step explanation:
assuming your trying to get to the equation y = mx+ b you have to set it like
(y - y1) = m(x - x1) first. (and you need the slope)
Find the slope:
y2 - y1 3 - 6 -3 3
---------- = --------- = -------- = -------- = 3
x2 - x1 -4 - (-3) -1 1
Now we plug in our equation:
( y - 6) = 3( x + 3)
(notice how I changed the ( x - x1) to a ( x + x1 ) because x1 in this case is negative and subtracting a negative is the same as adding)
Now we solve:
( y - 6) = 3( x + 3)
distribute the 3 to x and -3
( y - 6) = 3x -9
now add 6 to both sides to single out the y
y = 9x -3
Hope this helps <3
Also if that's wrong, I'm sorry and that just means you have to DIVIDE rather then add the 6. In which case, your answer would be y = 0.5x - 1.5 . If you need me to explain I can